Chinese Mustard Cultivation Guide for Florida - Yuheng Qiu; Mary Dixon; Guodong Liu (EDIS)
Chinese mustard is a nutritious leafy vegetable in the family Brassicaceae. Chinese mustard also goes by many common names, such as brown mustard, mustard greens, leaf mustard, Indian mustard, Oriental mustard, and vegetable mustard. Although it is considered a weed in a few states, such as Michigan, this species is not listed as invasive in Florida and has been cultivated in several counties, including Levy, Palm Beach, and Miami-Dade. This new 8-page publication of the UF/IFAS Horticultural Sciences Department provides a short cultivation guide as well as information on the uses and marketability of Chinese mustard. Written by Yuheng Qiu, Mary Dixon, and Guodong Liu. https://edis.ifas.ufl.edu/hs1402